Cultivo e prospecção de lectinas e outras proteínas bioativas de Pleurotus ostreatus em diferentes substratos - Aguiar, Lorena Vieira Bentolila de (Bionorte, 2022)
Characteristics related to the cultivation of edible fungi can influence the composition of the mushrooms produced, both their nutritional aspects and the presence of enzymes and bioactive proteins such as lectins, whose expression may vary according to the substrate and strain used. To verify the influence of these processes, strains 474, 542, 885, and 1467 of Pleurotus ostreatus were cultivated using substrates formulations with açaí seeds, elephant grass, pineapple, marupá, and pine sawdust. Changes in substrates pre and post-cultivation, mushroom productivity, the influence of substrates and strains on the nutritional characteristics of mushrooms, and biological activities of proteins were evaluated. For production parameters, 542 and 1467 strains, cultivated in pineapple and elephant grass, stood out in terms of basidiocarp production. As for the nutritional characteristics, differences were observed in the basidiocarps (proteins/fibers) according to the strain and the substrate used, with emphasis on açaí, pineapple, and pine substrates. The mushrooms produced were subjected to protein extraction in water, saline, and phosphate buffer (with signs of lectins), and the extracts obtained were subjected to the detection of lectins, proteases, and antioxidant proteins, as well as inhibitors. In the protein activities, for hemagglutinating activity (AHE), only the 1467 strain showed AHE in the aqueous extract and phosphate buffer, from the cultivation in açaí and marupá, being observed the inhibition of AHE only in the aqueous extracts and in phosphate of 1467 cultivated in açaí, in front of lactose. Regarding the antioxidant activity, the aqueous extracts showed the greatest potential for ABTS•+ and aqueous extract of 474 in pineapple for DPPH•, the saline extracts for chelation, and the saline extracts of 542 in the reducing power. As for proteolytic activity, the saline extracts showed the highest activity, 474 in açaí, with greater inhibition of trypsin in aqueous extracts, with 474 in pineapple and 542 in açaí and pineapple. No α-amylase, α-glucosidase, and lipase inhibiting activities were observed. The influence of the extraction method, as well as the substrate and the strain used, is highlighted, with the P. ostreatus strains showing different proteins according to the combination of these factors, demonstrating that these variations interfere with the quality of mushroom as food and font of biomolecules.
Keywords: Fungicultura; Atividade hemaglutinante; Cogumelo ostra